Asesmen Perkembangan Kognitif Anak pada Pembelajaran PAI Model Pembelajaran Problem Based Learning Materi Akidah Akhlak di SDI Musra - Maria Widya Wanti; Eli Masnawati (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
Cognitive assessment is one of the most important components in a teaching and learning process. Cognitive assessment has a function, namely to see how much children understand and have skills in the material that has been given using the problem-based learning model. to make students more active in finding and solving problems. This research aims to analyze the cognitive assessment of the based learning learning model on moral aqidah material at SDI Musra. This research uses descriptive research methods. Data was collected through interviews, observation and documentation. And the research results show that the cognitive assessment of the learning model based on moral belief material at SDI Musra is quite good. However, it still needs to be improved because with improvements it will become more effective in measuring students' understanding and skills. To be able to improve the quality of the cognitive assessment model of problem-based learning on moral belief material, this can be done by analyzing the assessment data in more depth to determine students' understanding and skills more comprehensively. This cognitive assessment has a positive influence on achieving a cognitive development target, apart from that for teachers, students, or parents, which will become a reference for the growth of students whose further education will prepare them for a higher level.